ANALISIS KINERJA ATRIBUT PELAYANAN PADA RESTORAN KENTUCKY FRIED CHICKEN (KFC) DI KABUPATEN PRINGSEWU - Dwi Putri Arlitha; Agus Hudoyo; Ktut Muniarti (Lampung University, 2022)
This study aims to analyze the service attributes of the Kentucky fried chicken (KFC) fast food restaurant in Pringsewu Regency that need to be retained and upgraded their performance. This study used a survey method and was conducted by interviewing 22 types of attributes and 60 consumers using a questionnaire. Determination of the sample is done by probabilistic sampling technique and the analytical method uses questionnaire analysis using Validity Test, Reliability Test, and data analysis using Important Performance Analysis (IPA). Each attribute is assessed by the level of importance and performance of consumers using a Likert scale of 1-7. The results of the importance and performance scores of each attribute are then processed and entered into a Cartesian diagram which is divided into four quadrants. This study shows that of the 22 attributes studied, 13 types of attributes are considered essential and 9 attributes are considered to have satisfactory performance. The types of performance attributes that need to be retained are the taste of food, speed of service, cleanliness of the premises, employee friendliness, security, employee understanding of the product, the comfort of the premises, availability of parking spaces, and availability of seats. The attributes that must be upgraded in-service performance are price, toilet cleanliness, availability of a prayer room, and availability of air conditioning. Keywords: Attributes, performance, important performance analysis (IPA)